Endothelial Dysfunction in Human Diabetes Is Mediated by Wnt5a–JNK Signaling. Issue 3 (March 2016) - Bretón-Romero, Rosa; Feng, Bihua; Holbrook, Monika; Farb, Melissa G.; Fetterman, Jessica L.; Linder, Erika A.; Berk, Brittany D.; Masaki, Nobuyuki; Weisbrod, Robert M.; Inagaki, Elica; Gokce, Noyan; Fuster, Jose J.; et al.
Abstract : Objective—: Endothelial dysfunction is linked to insulin resistance, inflammatory activation, and increased cardiovascular risk in diabetes mellitus; however, the mechanisms remain incompletely understood. Recent studies have identified proinflammatory signaling of wingless-type family member (Wnt) 5a through c-jun N-terminal kinase (JNK) as a regulator of metabolic dysfunction with potential relevance to vascular function. We sought to gain evidence that increased activation of Wnt5a–JNK signaling contributes to impaired endothelial function in patients with diabetes mellitus. Approach and Results—: We measured flow-mediated dilation of the brachial artery and characterized freshly isolated endothelial cells by protein expression, eNOS activation, and nitric oxide production in 85 subjects with type 2 diabetes mellitus (n=42) and age- and sex-matched nondiabetic controls (n=43) and in human aortic endothelial cells treated with Wnt5a. Endothelial cells from patients with diabetes mellitus displayed 1.3-fold higher Wnt5a levels ( P =0.01) along with 1.4-fold higher JNK activation ( P <0.01) without a difference in total JNK levels. Higher JNK activation was associated with lower flow–mediated dilation, consistent with endothelial dysfunction ( r =0.53, P =0.02). Inhibition of Wnt5a and JNK signaling restored insulin and A23187-mediated eNOS activation and improved nitric oxide production in endothelial cells from patients with diabetes mellitus. In endothelial cells from nondiabetic controls, rWnt5a treatment inhibited eNOS activation replicating the diabetic endothelial phenotype. In human aortic endothelial cells, Wnt5a-induced impairment of eNOS activation and nitric oxide production was reversed by Wnt5a and JNK inhibition. Conclusions—: Our findings demonstrate that noncanonical Wnt5a signaling and JNK activity contribute to vascular insulin resistance and endothelial dysfunction and may represent a novel therapeutic opportunity to protect the vasculature in patients with diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.